2019
DOI: 10.1007/s10815-019-01493-y
|View full text |Cite
|
Sign up to set email alerts
|

An update on the aspects of Zika virus infection on male reproductive system

Abstract: Zika virus (ZIKV) is mainly transmitted through Aedes mosquito bites, but sexual and post-transfusion transmissions have been reported. During acute infection, ZIKV is detectable in most organs and body fluids including human semen. Although it is not currently epidemic, there is a concern that the virus can still reemerge since the male genital tract might harbor persistent reservoirs that could facilitate viral transmission over extended periods, raising concerns among public health and assisted reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 88 publications
(102 reference statements)
0
12
1
2
Order By: Relevance
“…Other studies conducted in Taiwan, Sri Lanka and Vietnam [13,14,29] have shown that larval indices may be closely related to the incidence of dengue epidemics and arboviruses. In Brazil, similar research was conducted in Rio de Janeiro, São Paulo and Maranhão [14,18,19]. These studies used the infestation index in isolation; this differs from the present study which shows that patterns of spatial distribution and risk levels from small territorial units of analysis (census tracts, for example), can indicate that these risks can be connected into larger units, especially amongst adjoining neighbourhoods.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Other studies conducted in Taiwan, Sri Lanka and Vietnam [13,14,29] have shown that larval indices may be closely related to the incidence of dengue epidemics and arboviruses. In Brazil, similar research was conducted in Rio de Janeiro, São Paulo and Maranhão [14,18,19]. These studies used the infestation index in isolation; this differs from the present study which shows that patterns of spatial distribution and risk levels from small territorial units of analysis (census tracts, for example), can indicate that these risks can be connected into larger units, especially amongst adjoining neighbourhoods.…”
Section: Discussioncontrasting
confidence: 54%
“…The team from Tahiti (French Polynesia) had played in the Pernambuco Arena in June 2013 and the viral phylogenetic study showed that the origin of the Brazilian strain was Asian, sharing a common ancestor circulating in French Polynesia [18]. The Zika virus may have probably been introduced in Pernambuco, which could explain the larger size of the epidemic in this state and neighbouring areas, such as Campina Grande [19]. Zika virus was associated with a high prevalence of cases of congenital syndrome Zika, which has led the country to an emergency public health situation [20].…”
Section: Methodsmentioning
confidence: 99%
“…In these models, ZIKV infects and replicates in a variety of testicular cell types, including interstitial Leydig cells, Sertoli cells (SCs), and germ cells, and can cause testicular damage and reduction in motile sperms, resulting in infertility in male mice [16,17,19]. Several reports have revealed that SCs, which constitute the BTB, are highly susceptible to ZIKV infection, likely because they express high levels of AXL [23], a host molecule reported to be a possible attachment receptor or key factor promoting ZIKV infection [24]. Thus, SCs may act as a reservoir for long-term replication of virus in the testes, allowing ZIKV to continually infect germ cells and developing spermatocytes, even after peripheral clearance [25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SCs may act as a reservoir for long-term replication of virus in the testes, allowing ZIKV to continually infect germ cells and developing spermatocytes, even after peripheral clearance [25]. Recent studies have shown that ZIKV RNA can persist in human male semen up to 188 days after the onset of infection [23] illustrating its ability to pass through the BTB and disseminate into male reproductive tract [26]. Moreover, Govero et al also found that the prolongation of ZIKV infection is accompanied by the loss of BTB integrity [16].…”
Section: Introductionmentioning
confidence: 99%
“…The virus is also present in urine samples of ZIKV patients even after the onset of symptoms. Current evidence suggests that kidney tissue is a suitable environment for the replication of the virus [66,67].…”
Section: Non-vector Borne Transmissionsmentioning
confidence: 99%